Implementation of the Project Based Learning Model in Catholic Religious Education - Preti Anggraini; Paulina Maria Ekasari Wahyuningrum; Emilianus Sember Sawo (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study describes the implementation of the Project Based Learning (PjBL) model in Catholic Religious Education at Santo Paulus Catholic Junior High School, Palangka Raya. A qualitative descriptive design was used to understand the phenomenon in its natural setting. Data were collected from three informants, two Catholic Religious Education teachers and one principal, through interviews and documentation, supplemented by a questionnaire distributed to forty-four students, then analysed through data reduction, display, and conclusion drawing. The findings show that PjBL was implemented through six systematic steps, with Catholic faith values integrated at every stage. Project forms included videos, posters, Scripture drama, wall magazines, and social and environmental action, of which the latter were most meaningful. Student involvement was generally high, with active participation and good collaboration, although roughly thirty percent remained passive. Supporting factors included adequate facilities and parental support, whereas inhibiting factors involved limited time and uneven participation